Analysis of the Word Teleios in Matthew 5:48 and its Implications for the Congregation of the Voice of Truth Gospel Church in Medan - Rinto Francius Sirait (International Journal of Christian Education and Philosophical Inquiry, 2025)
The formation of a perfect character is the main goal for every believer, as stated in Matthew 5:48. The perfect phrase in this verse comes from the word τέλειος (teleios), and based on this, it is important to understand the word τέλειος (teleios) holistically, so that the congregation can understand correctly what God wants in their lives. The research method used in this study is the library research method, and therefore there is no population and sample used in this study, however, in this study the researcher will use various kinds of literature as references, such as: the Bible in various translations; Bible Dictionary; Language Dictionary; Encyclopedia; Concordance; Bible Interpretation Books; Other books related to the research theme; Journals and other literature related to the research theme. The data analysis technique used in this study is Theoretical Hermeneutics. Based on the results of the data analysis, it is known that the phrase τέλειος does not refer to a state of sinlessness, but to a real and profound transformation of life as a result of knowing God. The demand to be perfect in Matthew 5:48 means that God's people are called to emulate God's character, namely love that comes from a loving heart must be expressed concretely in everyday social life. The impact of implementing the Matthew 5:48 teaching model on the GSKI congregation in Medan City is seen in: The congregation's increasing strength in facing life's processes and worldly temptations; Firmness of faith marked by increased joy and strength in facing life's challenges; Spiritual independence seen from the congregation's ability to control ego/flesh, as well as growing a deep longing to live close to God.